Respostas
respondido por:
1
Método da Adição:
2x + 3y = 8 (2)
5x - 2y = 1 (3)
4x + 6y = 16
15x - 6y = 3 (+)
19x = 19
x = 19/19
x = 1
Substituir "X" em I:
2x + 3y = 8
2.1 + 3y = 8
2 + 3y = 8
3y = 8 - 2
3y = 6
y = 6/3
y = 2
2x + 3y = 8 (2)
5x - 2y = 1 (3)
4x + 6y = 16
15x - 6y = 3 (+)
19x = 19
x = 19/19
x = 1
Substituir "X" em I:
2x + 3y = 8
2.1 + 3y = 8
2 + 3y = 8
3y = 8 - 2
3y = 6
y = 6/3
y = 2
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
10 anos atrás